LANDING STRATEGY OF SQUIDS FROZEN IN MUARA ANGKE FISHING PORT, JAKARTA - Hutagalung, Revica Rosye; Wiyono, Eko Sri; Simbolon, Domu; Muninggar, Retno (Departemen PSP IPB, 2025)
One of the biggest commodities in PPN Muara Angke is squid. The condition of Muara Angke port has a floor with black puddles and a bad smell. The unloading workers do not use boots and afron when unloading. Smoking behavior of unloading workers is still found at the frozen squid landing site. The study used a quantitative descriptive analysis approach and SWOT analysis in analyzing the landing of frozen squid at PPN Muara Angke. The results showed that the handling of frozen squid at PPN Muara Angke offers a comprehensive view of the internal and external factors that influence the frozen squid handling activities at Muara Angke fishing port. Responding to these conditions requires an integrated strategy of internal strengths and external opportunities, as well as addressing internal weaknesses to overcome external threats. For example, by optimizing the unloading porters' ability to understand frozen squid quality standards, establishing partnerships with the fishery product processing industry, and strengthening the implementation of SOPs and supervision. Thus, it is expected that these strategies can improve the competitiveness and efficiency of frozen squid handling at PPN Muara Angke, as well as maintain product quality and operational sustainability. Key words: frozen squid, handling, Muara Angke Fishing Port, SWOT